Grammatical skills of Dutch children with 22q11.2 Deletion Syndrome in comparison with children with Developmental Language Disorder: Evidence from spontaneous language and standardized assessment - Boerma, Tessel; Everaert, Emma; Vlieger, Dinte; Steggink, Maaike; Selten, Iris; Houben, Michiel; Vorstman, Jacob; Gerrits, Ellen; Wijnen, Frank (Frontiers in Communication, 2023)
Background. Virtually all children with 22q11.2 Deletion Syndrome (22q11DS) experience language difficulties, next to other physical and psychological problems. However, the grammatical skills of children with 22q11DS are relatively unexplored, particularly in naturalistic settings. The present research filled this gap, including two studies with different age groups in which standardized assessment was complemented with spontaneous language analysis. In both studies, we compared children with 22q11DS to children with Developmental Language Disorder (DLD), for whom the origin of language difficulties is unknown. Methods. The first study included 187 preschool children (n=44 with 22q11DS, n=65 with DLD, n=78 typically developing; TD). Standardized assessment consisted of grammar and vocabulary measures in both expressive and receptive modality. Spontaneous language during a play session was analyzed for a matched subsample (n=27 per group). The second study included 29 school-aged children (n=14 with 22q11DS, n=15 with DLD). We administered standardized tests of receptive vocabulary and expressive grammar, and elicited spontaneous language with a conversation and narrative task. In both studies, spontaneous language measures indexed grammatical accuracy and complexity. Results. Spontaneous language analysis in both studies did not reveal significant differences between the children with 22q11DS and peers with DLD. The preschool study showed that these groups produced less complex and more erroneous utterances than TD children, who also outperformed both groups on the standardized measures, with the largest differences in expressive grammar. The children with 22q11DS scored lower on the receptive language tests than the children with DLD, but no differences emerged on the expressive language tests. Discussion. Expressive grammar is weak in both children with 22q11DS and children with DLD. Skills in this domain did not differ between the groups, despite clear differences in etiology and cognitive capacities. This was found irrespective of age and assessment method, and highlights the view that there are multiple routes to (impaired) grammar development. Future research should investigate if interventions targeting expressive grammar in DLD also benefit children with 22q11DS. Moreover, our findings indicate that the receptive language deficits in children with 22q11DS exceed those observed in DLD, and warrant special attention.